2016
DOI: 10.1159/000442257
|View full text |Cite
|
Sign up to set email alerts
|

Association of Two Polymorphisms, rs1061170 and rs1410996, in Complement Factor H with Age-Related Macular Degeneration in an Asian Population: A Meta-Analysis

Abstract: Background: With the increasing number of studies indicating that two single-nucleotide polymorphisms (SNPs), rs1061170 and rs1410996, in complement factor H (CFH) might be associated with the susceptibility to age-related macular degeneration (AMD), the exact association still remains uncertain. Thus, we conducted a meta-analysis to systematically summarize and clarify the association between the two SNPs and the AMD risk particularly in an Asian population. Methods: A systematic search of studies on the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…; Wu et al. ), our results showed a significant association between the rs1061170 polymorphism and the risk of all AMD subtypes, with a summary allele OR of 2.15. However, our analysis indicated significant between‐study heterogeneity, with an I 2 measure that ranged from 81.2% to 92.4% in any genetic model.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…; Wu et al. ), our results showed a significant association between the rs1061170 polymorphism and the risk of all AMD subtypes, with a summary allele OR of 2.15. However, our analysis indicated significant between‐study heterogeneity, with an I 2 measure that ranged from 81.2% to 92.4% in any genetic model.…”
Section: Discussionsupporting
confidence: 61%
“…It has been observed that the strength of the association between rs1061170 polymorphism and AMD seems to be lower when studies move from the West to the East, and the compelling association, observed in European cohorts, was not as relevant to the AMD risk in populations of Asian ancestry (Wu et al. ). Individual studies have been performed in Asian populations, but most of these reported a lack of association in Korean, Japanese and Chinese (Chen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to age-related changes, it has been shown that genetic factors significantly contribute to risk for advanced AMD 10,11. About 20 genes involved in the pathogenesis of AMD have been identified, the most important being CFH , C3 , C2 , ARMS2 , FB , CFHR4 , CFHR5 , and F13B .…”
Section: Risk Factorsmentioning
confidence: 99%
“…23 A combination of drusen parameters along with other OCT derived parameters such as hyperreflective foci and retinal thickness may be the most informative and predictive of progression. 15,16,23 The association between advanced AMD and the CFH Y402H variant as well as the intronic SNP in this gene, CFH rs1410996, have been well documented 6,20,34,38,[49][50][51] The biologic mechanisms underlying their effect on drusen accumulation, however, have not been fully explored. In our previous analyses of these variants regarding progression, the effect of rs1410996 was stronger and the effect of Y402H was reduced when both were in the same model, suggesting that this variant may be more strongly associated with AMD.…”
Section: Discussionmentioning
confidence: 99%